Indicators of effectiveness of nursing care in the dimension of patient safety - Leila Soares Seiffert; Lillian Daisy Gonçalves Wolff; Maria Manuela Frederico Ferreira; Elaine Drehmer de Almeida Cruz; Alexandra Lunardon Silvestre (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to validate nursing care effectiveness indicators of patient safety dimension. Methods: quantitative survey, using the electronic Delphi sampli, with 52 participants selected by the Snowball sampling. Eight indicators were evaluated regarding the attributes: availability, reliability, simplicity, representativeness, sensitivity, comprehensiveness, objectivity, cost, utility, stability and timeliness. For validation, the minimum agreement criterion was 70%. Results: Cronbach's alpha (0.942) evidenced the high internal consistency among the attributes. The indicators fall with damage, hip fracture, and postoperative hip fracture, incidents related to equipment, incidents due to failures in patient identification, and pressure injury were validated in all attributes, and those of medication error and hand Hygiene were not validated. Conclusions: the validated indicators allow assessment of the effectiveness of hospital nursing care. Unavailability of data is an obstacle to monitoring patient safety.